Unaffordable medical scheme contributions: A barrier to access to private health cover in South Africa - T. Fish; S. Ramjee (South African Journal of Business Management, 2007)
The purpose of the Medical Schemes Act, No. 131 of 1998 was inter alia to `promote non discriminatory access to privately funded health care'. A number of reforms were proposed as steps on a path to Social Health Insurance (SHI) with the ultimate goal of the reforms being to increase the number of people contributing to a private financing mechanism, thereby reducing the burden on the public sector.The increase in health care costs over time has been the focal point of industry discussions regarding affordability. In recent years the industry has responded positively to the affordability challenge by developing new products aimed at the lower end of the market. With medical inflation as a significant challenge, this paper argues that in 2003 the cost of entry-level medical scheme options was largely unaffordable and that this state of affairs has not improved over time. The proportion of the population covered by medical schemes declined marginally during the time period under review (2003 – 2006), despite the regulatory environment.The analysis, done from the perspective of a prospective medical scheme member, aims to identify the proportion of medical scheme options affordable to each of four `benchmark' families.
Keywords: 650